1998
DOI: 10.1016/s0954-6111(98)90002-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cyclosporin A on inflammatory cytokine production by human alveolar macrophages

Abstract: Cyclosporin A (CsA) is an immunomodulator drug that has been used in the treatment of several types of advanced pulmonary interstitial disease. This beneficial effect occurs mainly in circumstances in which alveolitis due to CD4 lymphocytes is absent, suggesting that CsA acts on other types of cells. The present study was undertaken to determine the effect of CsA on inflammatory cytokine secretion by human alveolar macrophages (AMs). Human AMs were collected by bronchoalveolar lavage from four control subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…The mechanisms of this undesirable effect of FK506 are unknown. However, with respect to CsA, it has been shown to induce the production of pro-inflammatory cytokines in human airway epithelial cells in a dose-dependent manner [27], although other studies have indicated that CsA has inhibitory effects on the release of pro-inflammatory mediators and has T-lymphocyte-associated immunosuppressive actions [12]. These findings of acute injury phase could implicate that individuals who chronically receive FK506 as an immunosuppressive drug may be at greater risk for acute-lung injury and permeability-pulmonary oedema.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanisms of this undesirable effect of FK506 are unknown. However, with respect to CsA, it has been shown to induce the production of pro-inflammatory cytokines in human airway epithelial cells in a dose-dependent manner [27], although other studies have indicated that CsA has inhibitory effects on the release of pro-inflammatory mediators and has T-lymphocyte-associated immunosuppressive actions [12]. These findings of acute injury phase could implicate that individuals who chronically receive FK506 as an immunosuppressive drug may be at greater risk for acute-lung injury and permeability-pulmonary oedema.…”
Section: Discussionmentioning
confidence: 99%
“…FK506 is known to exhibit its pharmacological effects on inflammatory cells, including T-cells, macrophages [12], eosinophils [16] and neutrophils [17]. Little is known regarding the effect of FK506 on fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CsA is an immunomodulatory drug that plays a role in inhibiting the activation of helper T cells and alveolar macrophages (14), and has been used to treat several types of pulmonary interstitial diseases (15)(16)(17). The pathogenesis of OP remains speculative.…”
Section: Discussionmentioning
confidence: 99%
“…CsA was shown to block mitogen-induced production of the chemokines, IL-8 and IP-10, by human T cells (24), but had no effect on LPS-induced IL-8 production by human monocytes (25) and only modestly decreased production of IL-8 by LPS-treated alveolar macrophages (26). In contrast, CsA enhanced IL-1β-induced fibroblast production of IL-8 but decreased associated production of MCP-1 (27).…”
Section: Figurementioning
confidence: 98%